Boundary element formulation for dynamic analysis of inelastic structures - Czyż, Tomasz; Fedeliński, Piotr (Computer Assisted Methods in Engineering and Science, 2022)
The boundary element formulation for dynamic analysis of inelastic two-dimensional structures subjected to stationary or transient inertial loads is presented. The problem is solved by using simultaneously the displacement and stress integral equations. The numerical solutioll requires discretization of the boundary displacements and tractions, and stresses in the interior of the body. The boundary is divided into quadratic elements and the domain into constant or quadratic quadrilateral cells. The unknown stresses ill the coupled system of equations are computed using an iterative procedure. The mass matrix of the structure is formulated by using the dual reciprocity method. The matrix equation of motion is solved step-by-step by using the Houbolt direct integration method. Several numerical examples show the influence of the discretization on the accuracy and new applications of the method. The solutions are compared to the analytical results or those computed by the finite element method.